Inclusive Education in Primary and Secondary School: Perception of Teacher Training - Castillo-Guajardo, D (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Introduction. Inclusive education is one of the main objectives of the educational system toward achieving equal opportunities among students. To this end, teacher training plays an important role in the different educational stages. Objectives. To analyze the perceived readiness of teachers for inclusive education and to see the differences in primary and secondary education. Methods: A total of 961 active teachers from public schools, 53.3% Primary and 46.7% Secondary Education, were analyzed by means of a questionnaire on Teachers’ perceptions about their preparation for inclusive education and the CEFI-R instrument. Results. There are statistically significant differences between the two stages in the first questionnaire (question 1: p = 0.03; question 2: p < 0.01 and question 3: p < 0.01) and also, in 3 of the four CEFI-R dimensions, with the primary score being higher. Conclusions: This study shows that there is a large percentage of teachers who believe that their initial training is insufficient to deal with student diversity. In addition, most of them state that continuous training has helped them to improve inclusive education and that they would be willing to attend training courses on inclusion, although in secondary school, the predisposition is lower than in high school. On the other hand, teachers of both educational stages show a mostly favorable attitude according to the CEFI-R, being higher in primary than in secondary school. In this sense, the public administration has work to do. © 2022 by the authors.